Screening of Quorum Quenching Activity of Bacteria Isolated from Ant Lion - Billy Christianto; . Yogiara (Indonesian Society for microbiology, 2011)
Bacterial intercellular communication or quorum sensing controls the pathogenesis of many medically important organisms. Therefore, it is important to isolate bacteria that can disintegrate the communication, in a process called quorum quenching. Bacteria from ant lion (Myrmeleon sp.) were grown on Luria agar, and approximately 1.85 x 109 CFU mL-1 was obtained. Eleven morphologically different colonies were screened for quorum quenching activity using wild type Chromobacterium violaceum as an indicator. Two isolates (Myr7 and MyrB) were found to possess quorum quenching activity. Isolates with quorum quenching activity were later identified employing 16S rRNA. Both isolates were similar to bacteria in the genus Aeromonas